Hope, Mattering, and Pathways Towards Economic Agency among Financially Marginalized Adults - Amy Castro; Chenyi Ma; Claudette Grinnell Davis; Meagan Cusack (Social Work and Society, 2022)
Growing inequality and wealth depletion characterize the past three decades of life in the United States. In response, social work scholars developed financial capability and asset building interventions that account for structural market inequality. Yet, important constructs of hope (a sense of agency in the face of uncertainty) and mattering (awareness, importance, and reliance) may be missing from financial interventions. We employ a human capability approach for testing these assertions among 140 low-income adults participating in an economic mobility intervention. Bivariate simple regressions and multivariate sequential regressions assess the relationships between economic agency, mattering, religiosity and spirituality, and hope. Findings indicate that only reliance (the degree to which others voluntarily trust us) is associated with economic agency, suggesting that in a market where pathways out of poverty continue shrinking, meaningful human connection and relational vulnerability can return a measure of agency, humanity, and self-determination despite extreme market duress.